(untitled) (Research, Society and Development, 2022)
Obesity is caused by an increase in the mass of adipose tissue, being considered a multifactorial disease that can be avoided. The main triggering factor is energy imbalance, due to the high level of calories consumed and low energy activity. In Brazil, obesity grew by 67.8%, being one of the most significant factors in patients with COVID-19. COVID-19 (coronavirus disease 2019) is a respiratory infection caused by the SARS-CoV-2 coronavirus, which can progress from a flu to Severe Acute Respiratory Syndrome until death. The current pandemic has a recent onset and a rapid pace of development due to its high rate of transmission and global distribution. The body of scientific evidence is still sparse, each outbreak that arises is an opportunity to obtain more information about the virus. This work aims to contribute to increasing knowledge of the COVID-19 pandemic by evaluating the mortality rate from COVID-19 associated with obesity as a risk factor, observing the epidemiological bulletins from April 2020 to August 2021 of Coronavirus Disease 2019, with emphasis on deaths, according to age, sex and region of greatest prevalence. Thus, as a result of the collected data, it is observed that the Midwest region has the highest incidence, the male gender is more prevalent and obesity is the main risk factor for children under 60 years of age. Therefore, it is necessary for the country to intensify surveillance actions for aggravating factors, such as obesity, which is a modifiable risk factor.